Serum pepsinogens as a gastric cancer and gastritis biomarker in South and Southeast Asian populations - Miftahussurur, Muhammad (PLoS One, 2020)
Serum pepsinogens have been widely acknowledged as gastric mucosal biomarkers; however, a multicountry report on the benefits of pepsinogens as biomarkers has not yet been published. We analyzed 1,206 sera and gastric mucosal samples collected from Bangladesh, Bhutan, Indonesia, Myanmar, Nepal and Thailand then assessed the association between gastric mucosal changes and Helicobacter pylori infection. The new cutoff values for serum pepsinogen values were evaluated using a receiver operating characteristic analysis. The participants with H. pylori infection had significantly lower pepsinogen I and higher pepsinogen II values, but a lower pepsinogen I/II ratio than participants without the infection (all P < .001). The pepsinogen I and pepsinogen I/II values were significantly higher and lower, respectively, in individuals with atrophic gastritis than in those without (both P < .001). Among uninfected individuals, only the pepsinogen I/II ratio was significantly lower in atrophic individuals. Pepsinogen I/II ratio also were significantly different between disease among H. pylori-positive and H. pylori-negative individuals, suggesting the pepsinogen I/II ratio is a robust biomarker for determining both chronic and atrophic gastritis. The cutoffs for detecting chronic and atrophic gastritis for the pepsinogen I/II ratio were 4.65 and 4.95, respectively. In conclusion, pepsinogen levels are useful biomarker for both chronic gastritis and atrophic gastritis, but they should be used with caution. Population-based validation is necessary to determine the best cutoff values. Among all pepsinogen values, the pepsinogen I/II ratio was the most reliable gastric mucosal-change biomarker.